Pre-cooling with ice slurry ingestion leads to similar run times to exhaustion in the heat as cold water immersion - Siegel, R.; Maté, J.; Watson, G.; Nosaka, K.; Laursen, P. B. (Journal of Sports Sciences, 2012)
The purpose of this study was to compare the effects of pre-exercise ice slurry ingestion and cold water immersion on submaximal running time in the heat. On three separate occasions, eight males ran to exhaustion at their first ventilatory threshold in the heat (34.0 ± 0.1°C, 52 ± 3% relative humidity) following one of three 30 min pre-exercise manoeuvres: (1) ice slurry ingestion; (2) cold water immersion; or (3) warm fluid ingestion (control). Running time was longer following cold water immersion (56.8 ± 5.6 min; P = 0.008) and ice slurry ingestion (52.7 ± 8.4 min; P = 0.005) compared with control (46.7 ± 7.2 min), but not significantly different between cold water immersion and ice slurry ingestion (P = 0.335). During exercise, rectal temperature was lower with cold water immersion from 15 and 20 min into exercise compared with control and ice slurry ingestion, respectively, and remained lower until 40 min (P = 0.001). At exhaustion rectal temperature was significantly higher following ice slurry ingestion (39.76 ± 0.36°C) compared with control (39.48 ± 0.36°C; P = 0.042) and tended to be higher than cold water immersion (39.48 ± 0.34°C; P = 0.065). As run times were similar between conditions, ice slurry ingestion may be a comparable form of pre-cooling to cold water immersion.